(7r+5)(2r-6)=0

Simple and best practice solution for (7r+5)(2r-6)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7r+5)(2r-6)=0 equation:


Simplifying
(7r + 5)(2r + -6) = 0

Reorder the terms:
(5 + 7r)(2r + -6) = 0

Reorder the terms:
(5 + 7r)(-6 + 2r) = 0

Multiply (5 + 7r) * (-6 + 2r)
(5(-6 + 2r) + 7r * (-6 + 2r)) = 0
((-6 * 5 + 2r * 5) + 7r * (-6 + 2r)) = 0
((-30 + 10r) + 7r * (-6 + 2r)) = 0
(-30 + 10r + (-6 * 7r + 2r * 7r)) = 0
(-30 + 10r + (-42r + 14r2)) = 0

Combine like terms: 10r + -42r = -32r
(-30 + -32r + 14r2) = 0

Solving
-30 + -32r + 14r2 = 0

Solving for variable 'r'.

Factor out the Greatest Common Factor (GCF), '2'.
2(-15 + -16r + 7r2) = 0

Factor a trinomial.
2((-5 + -7r)(3 + -1r)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-5 + -7r)' equal to zero and attempt to solve: Simplifying -5 + -7r = 0 Solving -5 + -7r = 0 Move all terms containing r to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -7r = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -7r = 0 + 5 -7r = 0 + 5 Combine like terms: 0 + 5 = 5 -7r = 5 Divide each side by '-7'. r = -0.7142857143 Simplifying r = -0.7142857143

Subproblem 2

Set the factor '(3 + -1r)' equal to zero and attempt to solve: Simplifying 3 + -1r = 0 Solving 3 + -1r = 0 Move all terms containing r to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1r = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1r = 0 + -3 -1r = 0 + -3 Combine like terms: 0 + -3 = -3 -1r = -3 Divide each side by '-1'. r = 3 Simplifying r = 3

Solution

r = {-0.7142857143, 3}

See similar equations:

| (4-5i)/(5-1) | | 2z+13=8z+1 | | 2x-1+x=-28 | | 9y+8=6y+1 | | X+4-3=6*5 | | 2-x+6x=37 | | 42=(960)(177/360)r | | 4x+5ys=12 | | y+(-2)=100 | | 15+x=2x+6 | | -13=2x+5x+8 | | 71+[-5+(-2x+3)]=25-[-(3x+4)-(4x+3)] | | 5(p+2)+6(-3-p)=0 | | 7x^2-11x+5=0 | | 4x^2-80x+144=0 | | 4+6x+2x=76 | | 1+[-5+(-2x+3)]=25-[-(3x+4)-(4x+3)] | | y=7x+-10+-3 | | 5p^2-125=0 | | -3x+7-4x=-77 | | x+x+2+x+4=66-x | | 315=30z | | -8x^2+4x+5=0 | | 0=4x^2-81 | | 4x^6+x^3-6x^2-x^3-5x^2+3x= | | y=13+7x | | 2k-5=4k+3 | | x-10-x=8 | | -5×(1/3)^n-1 | | X-2y+2z=-1 | | r-6=7 | | 3x-8+4x=-22 |

Equations solver categories